Morphohistogenesis of trachea in goats (Capra hircus) - MALIK, M R; PILLAI, P V A; TALUJA, J S; PARMAR, M L (The Indian Journal of Animal Sciences, 2014)
The trachea was measured in 18 goat foeti of 4.00 - 35.00 cm CR length. The foetuses were divided into 3 groups on the basis of CR length. The length of trachea measured 25.00 ± 3.406 mm in group 1 and increased to 108.33 ± 7.149 mm in group 3. It was wider (5.66 ± 0.248 mm) than its height (5.25 ± 0.311 mm) in all the age groups. The wall-thickness of trachea (0.050 ± 0.012 mm) in group 1 increased to approximately double (1.06 ± 0.058 mm) in group 2. The extent of association of tracheal parameters with CR length decreased with the advancement of age. Regression coefficient revealed that the circumference was influenced maximum (4.050 mm) due to change in CR length in group 1. In the wall of the trachea the fibrocellular plates transformed into cartilaginous plates in right, left and ventral positions in group 1. These matured and attained typical cartilaginous structure in group 2. The mucosa lined by pseudostratified epithelium was smooth in group 1, got folded in group 2 and folds enlarged and epithelium well differentiated and organized in group 3. The glands in lamina propria/submucosa could not be seen in any of the groups.